Deleuze and performance - Cull, Laura (Edinburgh : Edinburgh University Press, 2009)
- Performing in the chaosmos : farts, follicles, mathematics and delirium in Deleuze / Herbert Blau ##- Act I Deleuze on theatre : Artaud, Beckett and Carmelo Bene. I Artaud BwO : the uses of Artaud's To have done with the judgement of god / Edward Scheer ; Expression and affect in Kleist, Beckett and Deleuze / Anthony Uhlmann ; A theatre of subtractive extinction : Bene without Deleuze / Lorenzo Chiesa ##- Interval. Performing, strolling, thinking : from minor literature to theatre of the future / Daniel Watt ; Off the beaten path or, notes towards a Heideggerian deterritorialisation : a response to Daniel Watt / Julian Wolfreys ##- Act II Confronting Deleuze and live performance. Becoming a citizen of the world : Deleuze between Allan Kaprow and Adrian Piper / Stephen Zepke ; Sub specie durationis / Matthew Goulish and Laura Cull ; Thinking through theatre / Maaike Bleeker ; Becoming-dinosaur : collective process and movement aesthetics / Anna Hickey-Moody ##- Interval. Of butterflies, bodies and biograms : affective spaces in performativities in the performance of Madama Butterfly / Barbara Kennedy ##- Act III A digital Deleuze : performance and new media. Like a prosthesis : critical performance à digital Deleuze / Timothy Murray ; Performance as the distribution of life : from Aeschylus to Chekhov to VJing via Deleuze and Guattari / Andrew Murphie ; The 'minor' arithmetic of rhythm : imagining digital technologies for dance / Stamatia Portanova.
Onderzoek KASK (1KA-OFVR)
boek